Nanoemulsions of synthetic rhamnolipids act as plant resistance inducers without damaging plant tissues or affecting soil microbiota - Mottola, Milagro; Bertolino, María C.; Kourdova, Lucille Tihomirova; Valdivia Pérez, Jessica Aye; Bogino, María Florencia; Nocelli, Natalia E.; Chaveriat, Ludovic; Martin, Patrick; Vico, Raquel V.; Fabro, Georgina; Fanani, María Laura (Frontiers in Plant Science, 2023)
Plant pathogens and pests can cause significant losses in crop yields, affecting food security and the global economy. Many traditional chemical pesticides are used to combat these organisms. This can lead to the development of pesticide-resistant strains of pathogens/insects and negatively impact the environment. The development of new bioprotectants, which are less harmful to the environment and less likely to lead to pesticide-resistance, appears as a sustainable strategy to increase plant immunity. Natural Rhamnolipids (RL-Nat) are a class of biosurfactants with bioprotectant properties that are produced by an opportunistic human pathogen bacterium. RL-Nat can act as plant resistance inducers against a wide variety of pathogens. Recently, a series of bioinspired synthetic mono-RLs produced by green chemistry were also reported as phytoprotectants. Here, we explored their capacity to generate novel colloidal systems that might be used to encapsulate bioactive hydrophobic compounds to enhance their performance as plant bioprotectants. The synthetic mono-RLs showed good surfactant properties and emulsification power providing stable nanoemulsions capable of acting as bio-carriers with good wettability. Synthetic RLs-stabilized nanoemulsions were more effective than RLs suspensions at inducing plant immunity, without causing deleterious effects. These nanoemulsions were innocuous to native substrate microbiota and beneficial soil-borne microbes, making them promising safe bio-carriers for crop protection.